The Russians in Kant-Studien. Part 2 (1954—2010) - Salikov A. N. (Кантовский сборник, 2012)
This article is the second part of the research concerning the publications of Russian scholars in Kant-Studien, the leading periodical dedicated to Kantian studies and the most important print of International Kant Society. The article describes the history of publications of Russian authors from 1974 to 2008.